2016
DOI: 10.1128/msphere.00023-15
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Level Differences in Porphyrin Production and Regulation in Propionibacterium acnes Elucidate Disease Associations

Abstract: Propionibacterium acnes is a dominant bacterium residing on skin, and it has been thought to play a causal role in several diseases including acne, a common skin disease affecting more than 80% of people worldwide. While specific strains of P. acnes have been associated with either disease or healthy skin, the mechanisms remain unclear. Recently, we showed that vitamin B12 supplementation increased porphyrin production in P. acnes, leading to acne development (D. Kang, B. Shi, M. C. Erfe, N. Craft, and H. Li, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 44 publications
3
109
0
2
Order By: Relevance
“…For instance, small molecules, such as levulinic acid, able to inhibit porphyrin biosynthesis in acne‐associated C. acnes strains without disrupting the growth of health‐associated strains, are attractive drug candidates for the treatment of acne . Biofilms can also constitute novel targets to overcome increased resistance to antibiotics and restore a balanced cutaneous microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, small molecules, such as levulinic acid, able to inhibit porphyrin biosynthesis in acne‐associated C. acnes strains without disrupting the growth of health‐associated strains, are attractive drug candidates for the treatment of acne . Biofilms can also constitute novel targets to overcome increased resistance to antibiotics and restore a balanced cutaneous microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Among the differentially expressed microbial pathways, one significant feature of the disease state was the downregulation of vitamin B12 biosynthesis in C. acnes , which leads to the overproduction of the proinflammatory metabolites known as porphyrins . A follow‐up study comparing porphyrin production by individual C. acnes strains associated with either acne or healthy skin revealed that strains associated with healthy skin produced significantly lower amounts of porphyrins compared with acne‐associated strains, thus further supporting the different functions among C. acnes strains . A separate study reported the effect of isotretinoin treatment that showed clinical improvement and lowered levels of porphyrins in patients with acne .…”
Section: Acne and Skin Bacteriamentioning
confidence: 92%
“…produce porphyrins that can sometimes act as metal chelators and can also serve as inflammatory markers. 61 Increased porphyrin production in some strains over others are often associated with increased risk of acne or Staphylococcus aureus growth. Typically health-associated Propionibacterium strains produce less porphyrins than those associated with acne, suggesting that the ultimate difference between a “healthy” vs. “disease-inducing” bacteria lies in the metabolites produced.…”
Section: Dysbiosis and Homeostasismentioning
confidence: 99%
“…Typically health-associated Propionibacterium strains produce less porphyrins than those associated with acne, suggesting that the ultimate difference between a “healthy” vs. “disease-inducing” bacteria lies in the metabolites produced. 61 Likewise, Wollenberg et al showed that coproporphyrin III ( 16 ) produced by Propionibacterium acnes in the nasal cavity induce S. aureus virulence by enhancing S. aureus aggregation and biofilm formation. 59 Together with the knowledge that certain strains of Propionibacterium spp.…”
Section: Dysbiosis and Homeostasismentioning
confidence: 99%
See 1 more Smart Citation